2020
DOI: 10.3390/su12083466
|View full text |Cite
|
Sign up to set email alerts
|

Circular Economy Model: Insights from a Case Study in South Italy

Abstract: This study aims to analyze the economic and environmental sustainability of a case study of an energy power plant that produces electricity from pruning residues of olive groves from nine municipalities in southern Italy. To assess the economic sustainability of the agro-energetic chain, the profitability and efficiency ratios are calculated. Moreover, the GHG emissions of the agro-energetic pruning supply chain due to both the pruning collection at the field level, and their combustion for energy production a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Before trying to make a comparison with previous studies' results, it is important to underline that there are few examples in the literature with which to make a comparison with the present study, because, as reported by Palmieri et al [55], Fiusis represents a very particular power plant in the European context.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Before trying to make a comparison with previous studies' results, it is important to underline that there are few examples in the literature with which to make a comparison with the present study, because, as reported by Palmieri et al [55], Fiusis represents a very particular power plant in the European context.…”
Section: Discussionmentioning
confidence: 93%
“…Practically, this is not always true. For instance, Fiusis acknowledged that it can gather approximately 30% of the total annual biomass available in its supply basin [55], as not all farmers contribute to the supply of biomass. Hence, the overall estimated supply chain costs in B and C resulted as more trustable in the view of future development of the pruning supply chain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, and in the case of life cycle studies applied to olive oil production, the most challenging direction is to investigate which production methods can represent viable alternatives to optimize a functioning circular economic system by evaluating the way to convert agricultural by-products into energy or into valuable material fractions. For example, Palmieri et al [ 20 ] analyzed the economic and environmental sustainability of an agri-energy chain from pruning residues of olive groves in nine municipalities in southern Italy; Uceda-Rodríguez et al [ 21 ] evaluated the environmental benefits linked to the production of artificial inert materials created with olive pomace as an alternative to the final disposal of this waste in a landfill; Moreno et al [ 22 ] quantified environmental and economic indexes related to different innovative processes of the conversion of biomass coming from olive pruning residues into energy; finally, Batuecasa et al [ 23 ] conducted an LCA of olive oil production by-products by analyzing both anaerobic digestion and conventional disposal on the soil ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%